THE IMPACT OF ONLINE GAMBLING ON TEENAGERS IN TAPIAN NADENGGAN VILLAGE - Roi Marlan Siregar, Maysaroh Ritonga, Jailani Syahputra Siregar (STAI Syaichona Moh. Cholil Bangkalan, 2025)
The phenomenon of online gambling is increasingly widespread in Indonesia, including in ruralareas such as Tapian Nadenggan hamlet. This has various impacts, both from the educational,social, economic and religious fields. Teenagers are a group that is vulnerable to the influenceof online gambling because they are still in the emotional and cognitive development stage.Many of them fall into gambling as a form of entertainment or even as an attempt to gain instantfinancial gain. In Tapian Nadenggan Hamlet, this phenomenon is starting to attract publicattention. Some teenagers experience economic difficulties due to losing money in gambling.Based on these problems, this research aims to analyze the impact of online gambling onteenagers in Tapian Nadenggan Hamlet. This research aims to determine the factors thatencourage teenagers in Tapian Nadenggan Hamlet to play online gambling and to determine thesocial, economic, religious and educational impacts caused by online gambling.